Brichta Jindřich (1897-1957) - Kutil, Jiří (Iluminace, 2018)
Jiří Kutila's text, based on a description of personal collections stored in the National Film Archive and the National Technical Museum, maps the life and legacy of Jindřich Brichta, who rose from the profession of cinematographer and technical director to become a key figure in Czechoslovak film archiving, museum work, and education.
Keywords: Jindřich Brichta; National Film Archive; film museum; personal collection; film technology